Legal regulation of construction contract for relations in the Republic of Kazakhstan: a comparative analysis with the legislation of the CIS countries - Alimov, O.T.; Moroz, S.P.; Stepanova, T.V. (Bulletin of the Karaganda University “Law Series”, 2025)
The article explores the significance of contractual (construction) relationships and their legal regulation in accordance with the legislation of the Republic of Kazakhstan. A comparative analysis is conducted of certain aspects of the regulation of contractual relations in the Republic of Kazakhstan and the Commonwealth of Independent States (CIS) countries, such as the Republic of Azerbaijan, the Republic of Moldova, Ukraine, and the Russian Federation. The article analyzes legal provisions governing contractual relations, highlighting differences in legal regulation. International agreements and regulatory legal acts governing contractual relations both in the Republic of Kazakhstan and in CIS countries are examined. In addition, during the research process, the authors analyzed scholarly works focused on the legal aspects of the studied legal relations, which allowed for a deeper understanding and a comprehensive presentation of the topic. Particular attention is given to identifying the specific features of the legal regulation of contractual legal relations.